Neutrophil and endothelial adhesive function during human fetal ontogeny - Nußbaum, Claudia; Gloning, Anna; Pruenster, Monika; Frommhold, David; Bierschenk, Susanne; Genzel-Boroviczény, Orsolya; von Andrian, Ulrich H.; Quackenbush, Elizabeth; Sperandio, Markus (Journal of leukocyte biology, 2013)
Attenuation of the immune response contributes to the high rate of neonatal infections, particularly in premature infants. Whereas our knowledge of innate immune functions in mature neonates is growing, little is known about the ontogeny of neutrophil recruitment. We investigated neutrophils and ECs in the course of gestation with respect to rolling and adhesive functions. With the use of microflow chambers, we demonstrate that the neutrophilˈs ability to roll and adhere directly correlates with gestational age. These adhesion-related abilities are very rare in extremely premature infants (<30 weeks of gestation), which may correlate with our observation of markedly reduced expression of PSGL-1 and Mac-1 on neutrophils in preterm infants. In parallel, the capacity of HUVECs to mediate neutrophil adhesion under flow increases with gestational age. In addition, HUVECs from extremely premature infants exerting the lowest ability to recruit adult neutrophils show a diminished up-regulation of E-selectin and ICAM-1. Finally, by following neutrophil function postnatally, we show that maturation of PMN recruitment proceeds equivalently during extra- and intrauterine development. Thus, PMN recruitment and EC adhesion-related functions are ontogenetically regulated in the fetus, which might contribute significantly to the high risk of life-threatening infections in premature infants.